Pengaruh Kualitas Pelayanan Aparatur Pajak terhadap Kepuasan Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Penyuluhan dan Konsultasi Perpajakan (KP2KP) Piru - Latue, Linda Wati; Kainama, Maryoni Stevanny; Tomasoa, Theodora Florence (JENDELA PENGETAHUAN, 2025)
The quality of tax apparatus services plays a vital role in improving taxpayer compliance and satisfaction. This study aims to analyze the effect of tax apparatus service quality on the satisfaction of individual taxpayers at KP2KP Piru. A quantitative approach was employed by distributing questionnaires to 30 taxpayer respondents, with data analyzed using simple linear regression through SPSS version 26. The findings reveal that the quality of tax apparatus services has a positive and significant effect on taxpayer satisfaction. This result confirms that tangibles, reliability, responsiveness, assurance, and empathy dimensions contribute to increasing taxpayers’ satisfaction with the services received. In conclusion, improving service quality is a key factor in encouraging taxpayer compliance. The study implies that tax officers should enhance service speed, procedural consistency, and empathetic attitudes toward taxpayers. Recommendations are directed to tax institutions to continuously improve staff competence and provide more optimal service facilities.